Blood fluke exploitation of non-cognate CD4+ T cell help to facilitate parasite development. - Erika W Lamb; Colleen D Walls; John T Pesce; Diana K Riner; Sean K Maynard; Emily T Crow; Thomas A Wynn; Brian C Schaefer; Stephen J Davies (PLoS Pathogens)
Schistosoma blood flukes, which infect over 200 million people globally, co-opt CD4+ T cell-dependent mechanisms to facilitate parasite development and egg excretion. The latter requires Th2 responses, while the mechanism underpinning the former has remained obscure. Using mice that are either defective in T cell receptor (TCR) signaling or that lack TCRs that can respond to schistosomes, we show that naïve CD4+ T cells facilitate schistosome development in the absence of T cell receptor signaling. Concurrently, the presence of naïve CD4+ T cells correlates with both steady-state changes in the expression of genes that are critical for the development of monocytes and macrophages and with significant changes in the composition of peripheral mononuclear phagocyte populations. Finally, we show that direct stimulation of the mononuclear phagocyte system restores blood fluke development in the absence of CD4+ T cells. Thus we conclude that schistosomes co-opt innate immune signals to facilitate their development and that the role of CD4+ T cells in this process may be limited to the provision of non-cognate help for mononuclear phagocyte function. Our findings have significance for understanding interactions between schistosomiasis and other co-infections, such as bacterial infections and human immunodeficiency virus infection, which potently stimulate innate responses or interfere with T cell help, respectively. An understanding of immunological factors that either promote or inhibit schistosome development may be valuable in guiding the development of efficacious new therapies and vaccines for schistosomiasis.